Penerapan Model Pembelajaran Kooperatif Model STAD Untuk Meningkatkan Hasil Belajar Ekonomi Siswa Kelas XI MA - Ruaedah Kasim (Universtas Negeri Makassar, 2022)
The problem in this study is the low student learning outcomes in the Economics subject of Class XI Students at MA Almunawwarah Bottoe, Barru Regency. The approach used in this research is descriptive qualitative with this type of research is Classroom Action Research (CAR) which has a cycle which includes planning, implementation, observation, and reflection. The research setting was carried out in Class XI with the research subjects consisting of teachers and 15 students in class XI. Data collection techniques and procedures used were observation, tests, and documentation. The data analysis used is qualitative. The results showed that there was an increase in activity in teacher learning and student learning activities as well as learning outcomes in Economics, the increase could be seen from each cycle, namely in cycles 1 and 2. The conclusion in this study was that through the application of the STAD model cooperative learning model could improve learning outcomes. students in Economics class XI MA Almunawwarah Bottoe Barru Regency.